National Regulatory Approaches to Transnational Higher Education - Verbik, Line; Jokivirta, Lisa (International Higher Education, 2005)
Transnational higher education is not a new phenomenon, but the pace of its global expansion is a new development. (Transnational is used here to designate higher education provided by one country in another and excludes provision where just the students travel abroad.) As foreign delivery becomes increasingly widespread, countries are facing a growing need to regulate this type of provision. Although many countries have yet to establish a clear regulatory framework for the import and export of transnational higher education, ambitions to regulate and offer quality assurance for this type of provision are an emerging international trend.